2004
DOI: 10.1212/01.wnl.0000120671.73335.ec
|View full text |Cite
|
Sign up to set email alerts
|

Myoclonic status epilepticus following repeated oral ingestion of colloidal silver

Abstract: The authors report a case of a 71-year-old man who developed myoclonic status epilepticus and coma after daily ingestion of colloidal silver for 4 months resulting in high levels of silver in plasma, erythrocytes, and CSF. Despite plasmapheresis, he remained in a persistent vegetative state until his death 5.5 months later. Silver products can cause irreversible neurologic toxicity associated with poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 9 publications
1
50
1
2
Order By: Relevance
“…To our knowledge, this is the first report of corticobasal degeneration and myoclonic seizures associated with high levels of silver in serum. Our case differs from a previous report of myoclonic seizures in association with silver ingestion, 1 where the patient had used a homemade colloidal silver for four months. Our patient developed a slowly progressive neurodegenerative disorder over a period of four years, the onset of his symptoms following the commencement of his self-medication with a colloidal silver preparation.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, this is the first report of corticobasal degeneration and myoclonic seizures associated with high levels of silver in serum. Our case differs from a previous report of myoclonic seizures in association with silver ingestion, 1 where the patient had used a homemade colloidal silver for four months. Our patient developed a slowly progressive neurodegenerative disorder over a period of four years, the onset of his symptoms following the commencement of his self-medication with a colloidal silver preparation.…”
Section: Discussioncontrasting
confidence: 99%
“…38 Although there is a lack of evidence regarding the relationship between NPs and CNS diseases in human studies to date, animal research suggests possible links. For example, Mirsattari et al 39 reported a case of a 71-year-old man who developed myoclonic status epilepticus and went into a coma after daily ingestion of colloidal silver for 4 months. High levels of silver were found in the plasma, erythrocytes, and CSF of the patient.…”
Section: Relationship Between Nms and Cns Dysfunctionmentioning
confidence: 99%
“…In the alternative medicine world, use of e.g. colloidal silver for oral intake is increasingly popular although the users might run a serious health risk (Mirsattari et al 2004).…”
Section: Introductionmentioning
confidence: 99%